2015
DOI: 10.3389/fpsyg.2015.00170
|View full text |Cite
|
Sign up to set email alerts
|

Modality of fear cues affects acoustic startle potentiation but not heart-rate response in patients with dental phobia

Abstract: The acoustic startle response (SR) has consistently been shown to be enhanced by fear-arousing cross-modal background stimuli in phobics. Intra-modal fear-potentiation of acoustic SR was rarely investigated and generated inconsistent results. The present study compared the acoustic SR to phobia-related sounds with that to phobia-related pictures in 104 dental phobic patients and 22 controls. Acoustic background stimuli were dental treatment noises and birdsong and visual stimuli were dental treatment and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…These findings are partially contradicted by Wannemüller et al’s study [ 13 ] where, despite observing a higher HR during auditory stimuli, the dentally phobic subjects rated visual stimuli as more subjectively anxiety-provoking. Extending the discrepancy, a further study showed that individuals with dental phobia assessed visual dental-related stimuli as more anxiety-provoking, while exposure to dental-related pictures provoked increased levels of HR in individuals with dental phobia and decreased levels of HR in the HCs with no differences in HR reactions observed between dentally phobic subjects and the HCs during exposure to dental-related sounds [ 14 ].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…These findings are partially contradicted by Wannemüller et al’s study [ 13 ] where, despite observing a higher HR during auditory stimuli, the dentally phobic subjects rated visual stimuli as more subjectively anxiety-provoking. Extending the discrepancy, a further study showed that individuals with dental phobia assessed visual dental-related stimuli as more anxiety-provoking, while exposure to dental-related pictures provoked increased levels of HR in individuals with dental phobia and decreased levels of HR in the HCs with no differences in HR reactions observed between dentally phobic subjects and the HCs during exposure to dental-related sounds [ 14 ].…”
Section: Introductionmentioning
confidence: 69%
“…The comparison of auditory to visual modalities yielded mixed results, the auditory modality was found to be more anxiety-provoking than the visual modality by Hilbert et al [ 12 ]; the authors found increased activation in the phobia-associated regions of the brain, using functional magnetic resonance imaging, in dentally phobic subjects relative to the HCs. Auditory stimuli were corroborated as more anxiety-provoking in a study carried out by Wannemüller et al [ 13 ], where dentally phobic subjects exhibited increased HR during auditory stimuli in comparison to visual ones. Similarly, Oosterink et al [ 15 ] reported that stimuli related to invasive dental procedures were very effective at eliciting anxious responses, with drilling sounds provoking more anxiety than the sight of the drill.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The startle response is, however, inhibited for pleasant images. These effects have been reliably replicated for pictures (Bradley et al, 2001;Buchanan et al, 2004;Cook et al, 1991;Guerra et al, 2012;Hamm et al, 1997;Wannemüller et al, 2015) and sounds Roy et al, 2009;Wannemüller et al, 2015) suggesting that during perceptual tasks, the startle blink reflex is modulated by the hedonic value of the encoded material. In imagery contexts, however, a different pattern has been observed.…”
Section: Introductionmentioning
confidence: 88%
“…More specifically, the startle eyeblink reflex is typically potentiated in the context of an aversive stimulus and inhibited in the context of an appetitive stimulus, e.g. 4 6 . These effects may be explained by a relative match or a mismatch between the subject’s motivational state induced by the emotional context and the defensive nature of the startle reflex 7 .…”
Section: Introductionmentioning
confidence: 99%